Menu Close

dx-cos-x-cosec-x-




Question Number 152291 by iloveisrael last updated on 27/Aug/21
 ∫ (dx/(cos x+cosec x)) =?
dxcosx+cosecx=?
Answered by puissant last updated on 27/Aug/21
I=∫(dx/(cosx+cosecx))  =∫((sinx)/(cosxsinx+1))dx = ∫((2sinx)/(sin2x+2))dx  =∫((sinx+cosx)/(sin2x+2))dx+∫((sinx−cosx)/(sin2x+2))dx  t=sinx−cosx → dt=(sinx+cosx)dx  t^2 =1−sin2x ⇒ sin2x= 1−t^2   u=sinx+cosx → −du=(sinx−cosx)dx  u^2 =1+sin2x → sin2x= u^2 −1    ⇒ I=∫(dt/(1−t^2 +2))−∫(du/(u^2 −1+2))  =∫(dt/(((√3))^2 −(t)^2 ))−∫(du/((u)^2 +(1)^2 ))  =(1/(2(√3)))ln∣(((√3)−t)/( (√3)+t))∣−arctan(u)+C    ∴∵I=(1/(2(√3)))ln∣(((√3)−(sinx−cosx))/( (√3)+(sinx−cosx)))∣−arctan(sinx+cosx)+C..
I=dxcosx+cosecx=sinxcosxsinx+1dx=2sinxsin2x+2dx=sinx+cosxsin2x+2dx+sinxcosxsin2x+2dxt=sinxcosxdt=(sinx+cosx)dxt2=1sin2xsin2x=1t2u=sinx+cosxdu=(sinxcosx)dxu2=1+sin2xsin2x=u21I=dt1t2+2duu21+2=dt(3)2(t)2du(u)2+(1)2=123ln3t3+tarctan(u)+C∴∵I=123ln3(sinxcosx)3+(sinxcosx)arctan(sinx+cosx)+C..

Leave a Reply

Your email address will not be published. Required fields are marked *